Influences on Al-Asma’i’s Critical Judgment (A Critical Study) - Kadhim Atiyah, Hussam ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Many judgments in ancient Arabic criticism were subject to various influences that significantly shaped the critical judgment of Arab scholars. These influences included religious and sectarian factors, political and intellectual orientations, tribal bias, and other external factors. This phenomenon is clearly evident in the critical judgments of Al-Asma’i, who issued evaluations influenced by such factors. These influences led him to adopt a critical approach that did not always align with his esteemed scholarly status. As a result, he often undervalued the contributions and status of many poets, accusing them unjustly due to religious or political reasons, tribal loyalties, or racial biases. At times, he would even revise his initial judgments for reasons seemingly tied to his occasionally unstable psychological state. Moreover, Al-Asma’i’s alignment with the caliph and his tendency to echo the ruler’s opinions also played a role in shaping his judgments—even if this meant contradicting his own established critical principles. However, there were instances where he adhered to objective scientific standards directly related to the essence of literary work itself—such as criteria of quality and quantitative measures—which he used to rank poets over one another.